(untitled) (Altre Modernità, 2025)
This article presents the DIETALY project, funded by the Italian Ministry of Education, which explores the intersection between language, translation and tourism promotion, highlighting how tourism is not only an economic sector but also a key player in the formation of cultural identities. Through a diachronic lens, the articles presented in this special issue explore the evolution of Italian tourism communication in English, focusing mainly on the work of ENIT, Italy’s national tourism agency, from the early 20th century to the post-war period. The DIETALY project examines the transformation that institutional tourism communication has undergone during this historical period by analysing a range of media, including written texts, images and audiovisual content. Using an interdisciplinary and multimodal methodology, the project examines how visual and verbal elements were combined to convey the image of Italy as a tourist destination abroad, adapting to the challenges posed by the economic crises and the Second World War. It highlights the resilience and adaptability of the tourism sector, which is also expressed in the strategic use of language. An interdisciplinary approach that integrates tourism studies, linguistics and translation studies, and history is essential to understanding tourism promotion in all its facets. This framework promotes deeper insights into how language shapes tourism experiences and offers new research opportunities by examining past practices to better understand today’s globalized tourism landscape.